PROFIT AND LOSS SHARING (PLS) IN NON INTEREST FINANCE: A VIABLE ALTERNATIVE TO INTEREST-BASED LENDING (AUN INTERNATIONAL CONFERENCE, 2025)
This paper explores the concept of Profit and Loss Sharing (PLS) in non interest finance as an alternative to conventional interest-based lending. Rooted in Islamic law (Shariah), PLS aims to promote equitable wealth distribution and ethical financial practices. By examining theoretical foundations, empirical studies, and methodological frameworks, this paper evaluates the viability of PLS mechanisms primarily mudarabah and musharakah as sustainable and socially responsible financial instruments. The study concludes that while PLS holds substantial promise,however practical implementation challenges must be addressed for broader adoption in modern financial systems.